Petroleum Hydrocarbon-Degrading Bacteria for the Remediation of Oil Pollution Under Aerobic Conditions: A Perspective Analysis - Xu, Xingjian; Liu, Wenming; Tian, Shuhua; Wang, Wei; Qi, Qige; Jiang, Pan; Gao, Xinmei; Li, Fengjiao; Li, Haiyan; Yu, Hongwen (Frontiers in Microbiology, 2018)
With the sharp increasing population and modernization of society, environmental pollution resulted from petroleum hydrocarbons is aggravating and needs to be remediated urgently. Petroleum hydrocarbon-degrading bacteria are ubiquitous in nature and can utilize these compounds as the sources of carbon and energy. Bacteria with such functions are often exploited for the bioremediation of petroleum oil contaminated environment. Recently, microbial remediation technology has developed rapidly in theory and technology and achieved some gratifying results. However, this technology is not omnipotent. It is affected by many environmental factors in the process of practical application, which limits the large-scale application of the technology. Herein, this paper focuses on the literatures reported on the usage of bacteria as biodegraders, discusses barriers of microbial technology, simultaneously, predicts development directions.